2020
DOI: 10.3389/fneur.2020.00727
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Spontaneous Brain Activity in Left-Onset Parkinson Disease: A Resting-State Functional MRI Study

Abstract: Objective: Motor asymmetry is characteristic in Parkinson disease (PD). This phenomenon is originated from uneven degeneration of bilateral substantia nigra. However, this asymmetry may not restrict to substantia nigra or striatum. We aimed to determine the effect of asymmetry on spontaneous brain activity across the whole brain. Methods: We consecutively recruited 71 patients with PD, as well as 35 healthy controls, and collected relevant demographic, clinical, and neuropsychological information. The PD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
2
5
1
Order By: Relevance
“…They found several abnormalities of gray matter volume also in the right hemisphere in LPD patients, but they did not identify any significant difference between the two PD groups or between the controls and the RPD patients (52). Two additional MRI studies using structural and functional imaging techniques also showed more impairments in LPD patients than in RPD patients (41,53). Our findings are consistent with the above studies; LPD patients may have more severe neurodegeneration or less compensation than RPD patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They found several abnormalities of gray matter volume also in the right hemisphere in LPD patients, but they did not identify any significant difference between the two PD groups or between the controls and the RPD patients (52). Two additional MRI studies using structural and functional imaging techniques also showed more impairments in LPD patients than in RPD patients (41,53). Our findings are consistent with the above studies; LPD patients may have more severe neurodegeneration or less compensation than RPD patients.…”
Section: Discussionsupporting
confidence: 88%
“…This phenomenon is not uncommon. Some previous studies using structural imaging and fMRI techniques failed to identify significant differences in the direct comparison between LPD and RPD patients, although these two groups showed different patterns of abnormalities compared with the controls (41,52,53,55). In the present study, both PD groups had an average disease duration of more than 6 years and an average Hoehn-Yahr stage higher than 2.…”
Section: Discussioncontrasting
confidence: 58%
“…Functional data was preprocessed using the rs-fMRI data processing assistant (DPABI_V4.3, Beijing, China) 1 base on the MATLAB 2013b 2 platform. The preprocessing steps are consistent with previous literature (Xue et al, 2019;Li K. et al, 2020;Sun et al, 2020;Wang et al, 2020). The specific steps are described below.…”
Section: Data Preprocessingmentioning
confidence: 83%
“…As a conventional fMRI-derived method, amplitude of low-frequency fluctuation (ALFF) serves as a quantifiable index by calculating low-frequency (0.01-0.08 Hz) BOLD fluctuations (10). Although most previous studies utilized ALFF to characterize regional neural activity in PD, the aberrant brain regions in their results were inconsistent (11)(12)(13). This issue is mainly ascribed to clinical heterogeneity, medication effects, or differences in inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%